Nutrition in the control of inflammation : emerging roles for the microbiome and epigenome - Ferguson, Bradley S.; Frese, Steven (Elsevier, Academic Press, an Imprint of Elsevier, 2025)
"Nutrition in the Control of Inflammation: Emerging Roles for the Microbiome and Epigenome is a comprehensive guide that delves into the intricate relationship between diet and inflammation to regulate inflammatory diseases. Divided into five insightful sections, this book provides an introduction to the microbiome and epigenome in nutrition, exploring the impact of diet, lifestyle, and the microbiome on the development of inflammatory diseases. With a focus on nutrition and the epigenome in metabolic and cardiovascular diseases, the chapters tackle crucial topics such as histone modifications, DNA methylation, and non-coding RNAs in disease progression. Addressing health disparities in diet, epigenetics, and gut microbes, this book is a valuable resource for nutrition researchers, nutritionists, postgraduate students, and professionals in related fields. From the multifactorial microbial networks shaping aging to practical applications for diet and lifestyle improvements, this book offers practical insights for enhancing microbial and epigenetic health." -- elsevier.com